Design and control of an anthropomimetic robotic leg - Leong, Hon Choong. (2011)
In this report design modification and motion control of an existing cable-driven anthropomimetic robotic leg is implemented. Human walking gait is studied so as to implement motion control on the anthropomimetic legs. For the existing system, relatively high tension ratio between the cables of knee joint at extreme angle, via points design has been proposed to direct the cable away from the axis of rotation. By introducing these via points, the perpendicular distance between the high tension cable to the axis of rotation is increased so as to reduce the tension ratio. Optimization is carried out to identify the location of the via points which minimize the tension ratio. Two different cable deflection schemes are analysed and compared: cables not constraint to the via point and cables constraint to the via point. Beside tension ratio, stiffness is also considered for the selection of the schemes. Experiment is carried out to validate the new design.